Aspek Hukum Standarisasi Produk di Indonesia dalam Rangka Masyarakat Ekonomi ASEAN - Deviana Yuanitasari; Helitha Novianty Muchtar (Fakultas Hukum Universitas Islam Indonesia, 2018)
Standardization is an important aspect for Indonesia in global market competition, especially in the MEA (ASEAN Economic Community). This study raises the issues of, first, the strategy to improve product quality through Product Standardization in Indonesia in relation to MEA from the perspective of consumer protection law. Second, how ASEAN MRA (Mutual Recognition Arrangement) is adopted by ASEAN countries in the framework of MEA. The method used in this study is a normative juridical method, which includes research on positive legal inventory, research on legal principles, and in concreto legal research as well as legal comparisons. The results indicate that, first, the strategy to improve product quality through national product standardization is done by harmonizing national regulations to accelerate trade relations and protection of the Southeast Asian market. Second, ASEAN MRA is adopted by ASEAN countries with the use of MRA at the regional level, which can be seen in practice in ASEAN. The MRA concept is used by ASEAN through the ASEAN Framework Agreement on Mutual Recognition Arrangements that is currently contained in the ASEAN MRA used to support the AFTA free trade regime that was established to actualize trade liberalization among ASEAN countries.